Stakeholder perceptions of mental health stigma and poverty in Uganda - Kizza Dorothy; Lund Crick; Kigozi Fred; Ssebunnya Joshua; Okello Elialilia (BMC, 2009)
Abstract Background World wide, there is plentiful evidence regarding the role of stigma in mental illness, as well as the association between poverty and mental illness. The experiences of stigma catalyzed by poverty revolve around experiences of devaluation, exclusion, and disadvantage. Although the relationship between poverty, stigma and mental illness has been documented in high income countries, little has been written on this relationship in low and middle income countries. The paper describes the opinions of a range of mental health stakeholders regarding poverty, stigma, mental illness and their relationship in the Ugandan context, as part of a wider study, aimed at exploring policy interventions required to address the vicious cycle of mental ill-health and poverty. Methods Semi-structured interviews and focus group discussions (FGDs) were conducted with purposefully selected mental health stakeholders from various sectors. The interviews and FGDs were audio-recorded, and transcriptions were coded on the basis of a pre-determined coding frame. Thematic analysis of the data was conducted using NVivo7, adopting a framework analysis approach. Results Most participants identified a reciprocal relationship between poverty and mental illness. The stigma attached to mental illness was perceived as a common phenomenon, mostly associated with local belief systems regarding the causes of mental illness. Stigma associated with both poverty and mental illness serves to reinforce the vicious cycle of poverty and mental ill-health. Most participants emphasized a relationship between poverty and internalized stigma among people with mental illness in Uganda. Conclusion According to a range of mental health stakeholders in Uganda, there is a strong interrelationship between poverty, stigma and mental illness. These findings re-affirm the need to recognize material resources as a central element in the fight against stigma of mental illness, and the importance of stigma reduction programmes in protecting the mentally ill from social isolation, particularly in conditions of poverty.